The Use of Ginger and Mineral Water to Reduce Delayed Onset Muscle Soreness at Post Anaerobic Exercises (Department of Physical Education, Sport, Health and Recreation, 2020)
Excessive anaerobic exercises might cause pain in the muscles or commonly called Delayed Onset Muscle Soreness (DOMS). One of the benefits of ginger can reduce pain. The purpose of this study was to determine the effect of giving mineral water and ginger drink to the reduction of DOMS after anaerobic excercises. Experimental research method was then conducted in this research. The respondents were students from the Faculty of Sports Science. The treatment consisted of providing mineral water, ginger drink and a 50-meter sprint test with 7 repetitions. Numerical Rating Scale was used to measure pain. T-test statistics was used as an analysis method. The results of this study indicate a significant difference between the use of mineral water and ginger drink in reducing DOMS in the sample group after anaerobic activity. The decrease in the group given ginger drinks was faster than those given mineral water. It can be summarized that there is a decrease in pain or DOMS by giving ginger drink and mineral water after doing anaerobic excercises.